Intestinal Virome in Patients With Alcoholic Hepatitis. Issue 6 (10th October 2020) - Jiang, Lu; Lang, Sonja; Duan, Yi; Zhang, Xinlian; Gao, Bei; Chopyk, Jessica; Schwanemann, Leila K.; Ventura‐Cots, Meritxell; Bataller, Ramon; Bosques‐Padilla, Francisco; Verna, Elizabeth C.; Abraldes, Juan G.; et al.
Abstract : Background and Aims: Alcoholic hepatitis (AH) is a severe manifestation of alcohol‐associated liver disease (ALD) with high mortality. Although gut bacteria and fungi modulate disease severity, little is known about the effects of the viral microbiome (virome) in patients with ALD. Approach and Results: We extracted virus‐like particles from 89 patients with AH who were enrolled in a multicenter observational study, 36 with alcohol use disorder (AUD), and 17 persons without AUD (controls). Virus‐like particles from fecal samples were fractionated using differential filtration techniques, and metagenomic sequencing was performed to characterize intestinal viromes. We observed an increased viral diversity in fecal samples from patients with ALD, with the most significant changes in samples from patients with AH. Escherichia ‐, Enterobacteria ‐, and Enterococcus phages were over‐represented in fecal samples from patients with AH, along with significant increases in mammalian viruses such as Parvoviridae and Herpesviridae . Antibiotic treatment was associated with higher viral diversity. Specific viral taxa, such as Staphylococcus phages and Herpesviridae, were associated with increased disease severity, indicated by a higher median Model for End‐Stage Liver Disease score, and associated with increased 90‐day mortality. Conclusions: In conclusion, intestinal viral taxa are altered in fecal samples from patients with AH and associated with disease severity and mortality. Our study describes an intestinal virome signature associated with AH.